OVERVIEW OF THE METHODS AND TOOLS FOR SITUATION IDENTIFICATION AND DECISION-MAKING SUPPORT IN THE CYBERPHYSICAL SYSTEM «SMART HOUSE» (Computer systems and information technologies, 2022)
The technology of a smart house is mostly understood as a system that combines a number of subsystems that provide comfortable living conditions for residents in the room and make it possible to significantly reduce energy costs. A house is called smart if it has a certain computer or control system for managing engineering equipment. "Smart House" should be designed so that all services can be integrated with each other with minimal costs (in terms of finances, time and effort), and their maintenance would be organized in an optimal way.The "Smart House" system should competently allocate resources, reduce operating costs and provide a clear control and management interface. Such an intelligent system should be able to recognize specific planned and emergency situations occurring in the home and respond to them (make decisions) in accordance with the given program. Therefore, today the urgent task is to recognize the situation and support decision-making in the "Smart House" cyber-physical system.The conducted overview of methods and tools for situation identification and decision-making support in the "Smart House" cyber-physical system showed that: in existing solutions, situation recognition occurs only for one of the groups of the system of managed housing functions or does not occur at all; existing solutions provide decision-making support for only one of the groups of the system of managed housing functions or do not provide it at all; the available solutions do not provide for the possibility of assessing the sufficiency of information for decision-making in the "Smart House" cyber-physical system.Therefore, there is a need to develop such methods and tools for situation identification and decision-making support in the "Smart House" cyber-physical system, which would: perform situation recognition for all 5 groups of the system of managed housing functions; provide the decision-making support for all 5 groups of the system of managed housing functions; perform an assessment of the sufficiency of information for making all decisions in the "Smart House" cyber-physical system, which will be the focus of the authors' further efforts.
Keywords: cyber-physical system; system of managed housing functions; housing microclimate management; housing lighting control; housing security system; management of multimedia systems of housing; control of household appliances and power grid of housing